Antioxidant activity, phenol total, and flavonoid total of green tea (Camellia sinensis (L.) O. Kuntze) from three West Java tea estate - Mimin Kusmiyati; Yayat Sudaryat; Isti Agnia Lutfiah; Ardi Rustamsyah; Dadan Rohdiana (Research Institute for Tea and Cinchona, 2015)
Green tea has bioactive component, it is polyphenol which has strong antioxidant. As the largest component of polyphenol, flavonoid is very effective as an antioxidant. The purpose of this study was to determine antioxidant activity, phenol total and flavonoid total in green tea from three different estates, they were Cikajang Kab. Garut, Taraju Kab. Tasikmalaya, and Ciwidey Kab. Bandung. The results of this study show that seven samples have good antioxidant activity, but green tea which came from Cikajang (P-IRT No. 810320501698) has the highest IC50 grade it was 21,44 μg/ml. Beside that samples from Cikajang (P-IRT No. 810320501698) has highest total phenol content it was 334,68± SD 0,89/100 g samples and also has the highest total flavonoid it was 0,34 mg Kuersetin/g samples ± SD 0,21. On the contrary, green tea which has the lowest IC50 grade came from Taraju, the grade was 28,03 μg/ml, the samples has the lowest total phenol content it was 208,91± SD 4,47 mgGAE/100 g, and also has the lowest total flavonoid it was 0,207 mg Kuersetin/g samples ± SD 0,00.